Aluminum nitride ceramic polishing process

By using a polishing liquid modified by composite abrasives and functional compound, the aluminum nitride ceramic substrate is polished, and the problems of low polishing rate and poor effect in the prior art are solved, and efficient and stable polishing effect is achieved.

CN119188588BActive Publication Date: 2025-03-25COFFEY MATERIALS TECH (ZHEJIANG) CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411256242.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2025-03-25
Estimated Expiration
2044-09-09

AI Technical Summary

Technical Problem

The existing aluminum nitride ceramic polishing liquid has defects such as low polishing rate, easy to form apparent defects, ionic pollution, etc., resulting in poor polishing effect.

Method used

A polishing liquid consisting of composite abrasives, oxidants, functional compounds and water is used. The composite abrasive is composed of alumina and functionalized silicon sol. The functional compounds contain long-chain quaternary ammonium salt groups and benzotriazole groups. The pH value of the polishing liquid is adjusted to 4-4.5 through organic acids.

Benefits of technology

The suspension stability and antibacterial properties of the polishing liquid are improved, the polishing rate and effect are enhanced, and the aluminum nitride ceramic substrate with small surface roughness and no scratches can be obtained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119188588B_ABST
    Figure CN119188588B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of grinding and polishing, and specifically relates to an aluminum nitride ceramic polishing process. The polishing process comprises the following steps: placing an aluminum nitride ceramic substrate on a polishing pad, adding a polishing liquid for polishing; the polishing liquid is made of the following components by weight: 15-20 parts of a composite abrasive, 2-4 parts of an oxidant, 8-10 parts of a functional compound and 60-70 parts of water are mixed into a solution, and an organic acid is used to adjust the pH value of the solution to 4-4.5; the polishing liquid provided by the present invention has good suspension stability and antibacterial properties, and the aluminum nitride ceramic substrate is polished by using the polishing liquid, has a high polishing rate, good polishing effect, and can obtain an aluminum nitride ceramic substrate with small surface roughness and no scratches.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of grinding and polishing, and in particular relates to a polishing process for aluminum nitride ceramics. Background Art

[0002] Aluminum nitride (AlN) single crystal is an ultra-wide bandgap semiconductor material with high breakdown field strength, high thermal conductivity, good thermal stability, and complete transparency in the visible light DUV band. It is widely used in integrated circuit technology fields such as microelectronics and optoelectronics. As the size of electronic devices decreases, the surface flatness of aluminum nitride wafers is required to reach the nanometer level with acceptable resolution. The processing of aluminum nitride wafers includes: cutting the ingot into wafers using diamond wire, removing the wire cutting marks on the surface of the cutting disc and leveling the grinding process, and removing the damaged layer and scratches left by grinding on the wafer surface. Polishing technology is particularly important in the processing of aluminum nitride wafers.

[0003] Chemical mechanical polishing (CMP) technology can not only achieve global flattening, but also has good processing performance and polishing speed. It mainly uses chemical corrosion and mechanical force to smooth the surface of the substrate material during the processing. The chemical mechanical polishing process includes rough grinding, medium grinding and fine polishing. Among them, fine polishing ultimately determines the quality of the chip surface. Chemical mechanical fine polishing liquid is one of the key influencing factors. The polishing liquid on the market currently has defects such as low polishing rate, easy formation of surface defects, and ion contamination.

[0004] Chinese patent application No. 202011483351.4 discloses a polishing liquid for aluminum nitride ceramic substrates, a preparation method thereof and a polishing method thereof. The polishing liquid is mainly composed of the following components by mass: 90-110 parts of aluminum oxide abrasive, 4-12 parts of dispersant and 850-950 parts of water; a pH adjuster is used to adjust the pH of the polishing liquid to 3-5; the polishing liquid can effectively polish the aluminum nitride ceramic substrate and reduce the surface roughness, but the polishing effect needs to be improved; Chinese patent application No. 202210372295.X discloses a An odorless aluminum nitride polishing liquid and its preparation method and application, the polishing liquid is composed of the following raw materials in mass concentration: 0.1-40% abrasive particles, 0.5-5% alcohol ether, 0.5-20% oxidant, 0.2-5% pH stabilizer, and the balance is deionized water; the pH value of the polishing liquid is 2.5-4.5; the polishing liquid is suitable for ultra-precision optical devices or semiconductor power devices on the surfaces of difficult-to-process nitrogen-containing compounds such as silicon nitride and aluminum nitride, and has the advantages of high cutting rate, stable surface quality, and long cycle life, and has no volatility and heavy metal pollution problems, but its polishing effect is poor. Therefore, it is urgent to develop a polishing liquid suitable for aluminum nitride ceramic substrates with good polishing effect. Summary of the invention

[0005] The purpose of the present invention is to provide an aluminum nitride ceramic polishing process in view of the deficiencies in the prior art. The polishing liquid provided by the present invention has good suspension stability and antibacterial properties. The aluminum nitride ceramic substrate is polished using the polishing liquid, and has a high polishing rate and good polishing effect, and can obtain an aluminum nitride ceramic substrate with a small surface roughness and no scratches.

[0006] The technical solution adopted by the present invention to achieve the above-mentioned purpose is:

[0007] A polishing process for aluminum nitride ceramics, comprising the following steps: placing an aluminum nitride ceramic substrate on a polishing pad, adding a polishing liquid for polishing; the polishing liquid is made of the following components in parts by weight: 15-20 parts of a composite abrasive, 2-4 parts of an oxidant, 8-10 parts of a functional compound and 60-70 parts of water are mixed into a solution, and an organic acid is used to adjust the pH value of the solution to 4-4.5.

[0008] Further, the composite abrasive is composed of aluminum oxide and functionalized silica sol in a mass ratio of 1:1-2;

[0009] Furthermore, the alumina is spherical alumina, and the particle size of the spherical alumina is 80-100 nm.

[0010] Furthermore, the oxidant is one or a mixture of hydrogen peroxide, sodium hypochlorite, and potassium permanganate.

[0011] Furthermore, the organic acid is one or a mixture of tartaric acid, oxalic acid and citric acid.

[0012] Furthermore, in the polishing process, the polishing pad is a non-woven polishing cloth, and the polishing pressure is 200-300 g / cm 2 , the polishing speed is 80-100r / min, the polishing time is 50-60min, and the polishing liquid flow rate is 10-15mL / min.

[0013] In the technical solution of the present invention, the preparation method of the functionalized silica sol is:

[0014] S1. Add dopamine hydrochloride to the silica sol, disperse it evenly, add Tris solution, adjust the pH value of the solution to 8.5, place it at room temperature, stir and react for 24-30 hours to obtain polydopamine-modified silica sol;

[0015] S2. Add the functional compound and triethylamine to the polydopamine-modified silica sol obtained in step S1, maintain the reaction temperature at 80° C., and reflux for 4-5 hours. After the reaction is completed, a functionalized silica sol is obtained.

[0016] Furthermore, the particle size of the nano-silicon dioxide in the silica sol in step S1 is 10-20 nm; and the mass ratio of the silica sol to dopamine hydrochloride is 1:0.1-0.2.

[0017] Furthermore, in step S2, the mass ratio of the polydopamine-modified silica sol, the functional compound, and triethylamine is 1:0.05-0.1:0.025-0.05.

[0018] In the technical solution of the present invention, the preparation method of the functional compound is:

[0019] (1) Add 6-chloro-1-hydroxybenzotriazole and dodecyldimethyl tertiary amine to ethanol, maintain the reaction temperature at 80° C., reflux for 10-12 hours, and after the reaction is completed, cool to room temperature, remove ethanol, extract with dichloromethane and water, collect the aqueous phase, and concentrate under reduced pressure to obtain a modified compound with the structural formula:

[0020]

[0021] (2) Add the modified compound, 4-chlorobutyric acid and p-toluenesulfonic acid to toluene, maintain the reaction temperature at 110° C., reflux for 4-6 hours, and collect the water generated by the reaction with a water separator. After the reaction is completed, cool to room temperature, remove toluene, extract with dichloromethane and water, collect the aqueous phase, and concentrate under reduced pressure to obtain a functional compound with the structural formula:

[0022]

[0023] Furthermore, in step (1), the molar ratio of 6-chloro-1-hydroxybenzotriazole to dodecyldimethyl tertiary amine is 1:1.0-1.1.

[0024] Furthermore, the molar ratio of the modified compound in step (2), 4-chlorobutyric acid, and p-toluenesulfonic acid is 1:1.0-1.1:0.03-0.05.

[0025] The present invention has the following beneficial effects:

[0026] In order to obtain a polishing liquid with stable performance, the present invention uses 6-chloro-1-hydroxybenzotriazole as a raw material, reacts with dodecyl dimethyl tertiary amine and 4-chlorobutyric acid in sequence, and obtains a functional compound containing a long-chain quaternary ammonium salt group with antibacterial and dispersing effects and a benzotriazole group with antibacterial and chelating ion effects in the structure; on the other hand, silica sol is modified, and polydopamine with antibacterial effects and functional compounds with multiple functional effects are grafted on the surface of silicon dioxide in the silica sol in sequence, and functionalized silica sol is obtained; the present invention adds the functional compound and the functionalized silica sol into the polishing liquid components, and the two can act synergistically to improve the suspension stability and antibacterial performance of the polishing liquid, reduce ion contamination, make each component exist uniformly and stably in the polishing process, give full play to the effects of the composite abrasive and the oxidant, and thus help to improve the polishing rate and the polishing effect.

[0027] The polishing liquid provided by the present invention contains a composite abrasive composed of aluminum oxide and functionalized silica sol, an oxidant, a functional compound and water, and has good suspension stability and antibacterial performance; the present invention uses the polishing liquid to polish the aluminum nitride ceramic substrate, has a high polishing rate, good polishing effect, and can obtain an aluminum nitride ceramic substrate with small surface roughness and no scratches. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a morphology photograph of the surface of the aluminum nitride ceramic substrate under an atomic force microscope after polishing in Example 2 of the present invention. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present application will be clearly and completely described below in combination with the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments; the technical features designed in different implementation modes of the present invention described below can be combined with each other as long as they do not conflict with each other; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0030] In the technical scheme of the present invention, the chemical reagents used are all commercially available, wherein the solid content in the silica sol is 30%; 6-chloro-1-hydroxybenzotriazole CAS No. 26198-19-6; dodecyl dimethyl tertiary amine CAS No. 112-18-5; 4-chlorobutyric acid CAS No. 627-00-9; p-toluenesulfonic acid CAS No. 104-15-4; dopamine hydrochloride CAS No. 62-31-7; triethylamine CAS No. 121-44-8; hydrogen peroxide CAS No. 7722-84-1; sodium hypochlorite CAS No. 7681-52-9; potassium permanganate CAS No. 7722-64-7; tartaric acid CAS No. 526-83-0; malic acid CAS No. 6915-15-7; oxalic acid CAS No. 144-62-7; citric acid CAS No. 77-92-9.

[0031] Example 1

[0032] This embodiment provides a method for preparing a functional compound:

[0033] (1) Add 20.0 g of 6-chloro-1-hydroxybenzotriazole and 25.2 g of dodecyl dimethyl tertiary amine to 600 mL of ethanol, maintain the reaction temperature at 80° C., and reflux for 12 h. After the reaction is completed, cool to room temperature, remove ethanol, extract with dichloromethane and water, collect the aqueous phase, and concentrate under reduced pressure to obtain 36.4 g of the modified compound. The molar ratio of 6-chloro-1-hydroxybenzotriazole to dodecyl dimethyl tertiary amine is 1:1.0. The reaction process is:

[0034]

[0035] Modified compound: ESI (m / z): 383.9 [M+H] + , 1 H-NMR (600MHz, DMSO-d6, δppm): 12.42 (s, 1H), 7.96 (d, J=8.5Hz, 1H), 7.72 (s, 1H), 7.19 (d, J=8.5Hz , 1H), 3.73 (s, 6H), 3.21-3.23 (m, 2H), 1.72-1.74 (m, 2H), 1.26-1.30 (m, 18H), 0.88 (t, J=6.3Hz, 3H).

[0036] (2) Add 20.0 g of the modified compound, 6.4 g of 4-chlorobutyric acid and 0.45 g of p-toluenesulfonic acid to 250 mL of toluene, maintain the reaction temperature at 110° C., reflux for 6 h, and collect the water generated by the reaction with a water separator. After the reaction is completed, cool to room temperature, remove toluene, extract with dichloromethane and water, collect the aqueous phase, and concentrate under reduced pressure to obtain 21.5 g of the functional compound. The molar ratio of the modified compound, 4-chlorobutyric acid and p-toluenesulfonic acid is 1:1.0:0.05; the reaction process is:

[0037]

[0038] Functional compound: ESI (m / z): 488.5 [M+H] + , 1 H-NMR (600MHz, DMSO-d6, δppm): 7.95 (d, J=8.5Hz, 1H), 7.72 (s, 1H), 7.20 (d, J=8.5Hz, 1H), 3.69-3.72 (m, 8H), 3.21 -3.23 (m, 2H), 2.30-2.33 (m, 2H), 1.84-1.87 (m, 2H), 1.71-1.74 (m, 2H), 1.26-1.30 (m, 18H), 0.88 (t, J=6.3Hz, 3H).

[0039] Example 2

[0040] A polishing process for aluminum nitride ceramics comprises the following steps: placing an aluminum nitride ceramic substrate on a polishing pad, adding a polishing liquid for polishing; the polishing pad is a non-woven polishing cloth, and the polishing pressure is 300 g / cm 2 , the polishing speed is 90r / min, the polishing time is 50min, and the polishing liquid flow rate is 13mL / min.

[0041] The polishing liquid is made of the following components in parts by weight: 20 parts of composite abrasive, 4 parts of oxidant, 9 parts of functional compound and 70 parts of water are mixed into a solution, and the pH value of the solution is adjusted to 4.5 with an organic acid; the composite abrasive is composed of aluminum oxide and functionalized silica sol in a mass ratio of 1:2; the aluminum oxide is spherical aluminum oxide, and the particle size of the spherical aluminum oxide is 100 nm; the oxidant is hydrogen peroxide; and the organic acid is tartaric acid.

[0042] The preparation method of functionalized silica sol is as follows:

[0043] S1. Add dopamine hydrochloride to the silica sol, disperse it evenly, add Tris solution, adjust the pH value of the solution to 8.5, place it at room temperature, stir and react for 30 hours to obtain polydopamine-modified silica sol; the particle size of nano-silica in the silica sol is 20 nm; the mass ratio of silica sol to dopamine hydrochloride is 1:0.2;

[0044] S2. Add the functional compound and triethylamine to the polydopamine-modified silica sol obtained in step S1, maintain the reaction temperature at 80°C, and reflux for 5 hours. After the reaction is completed, a functionalized silica sol is obtained; the mass ratio of the polydopamine-modified silica sol, the functional compound, and the triethylamine is 1:0.1:0.05.

[0045] Example 3

[0046] A polishing process for aluminum nitride ceramics comprises the following steps: placing an aluminum nitride ceramic substrate on a polishing pad, adding a polishing liquid for polishing; the polishing pad is a non-woven polishing cloth, and the polishing pressure is 250g / cm 2 , the polishing speed is 100r / min, the polishing time is 60min, and the polishing liquid flow rate is 15mL / min.

[0047] The polishing liquid is made of the following components in parts by weight: 18 parts of composite abrasive, 3 parts of oxidant, 10 parts of functional compound and 65 parts of water are mixed into a solution, and the pH value of the solution is adjusted to 4 with an organic acid; the composite abrasive is composed of aluminum oxide and functionalized silica sol in a mass ratio of 1:1.5; the aluminum oxide is spherical aluminum oxide, and the particle size of the spherical aluminum oxide is 90nm; the oxidant is sodium hypochlorite; and the organic acid is citric acid.

[0048] The preparation method of functionalized silica sol is as follows:

[0049] S1. Add dopamine hydrochloride to the silica sol, disperse it evenly, add Tris solution, adjust the pH value of the solution to 8.5, place it at room temperature, stir and react for 24 hours to obtain polydopamine-modified silica sol; the particle size of nano-silica in the silica sol is 10 nm; the mass ratio of silica sol to dopamine hydrochloride is 1:0.1;

[0050] S2. Add the functional compound and triethylamine to the polydopamine-modified silica sol obtained in step S1, maintain the reaction temperature at 80°C, and reflux for 4 hours. After the reaction is completed, a functionalized silica sol is obtained; the mass ratio of the polydopamine-modified silica sol, the functional compound, and the triethylamine is 1:0.05:0.025.

[0051] Example 4

[0052] A polishing process for aluminum nitride ceramics comprises the following steps: placing an aluminum nitride ceramic substrate on a polishing pad, adding a polishing liquid for polishing; the polishing pad is a non-woven polishing cloth, and the polishing pressure is 200 g / cm 2 , the polishing speed is 80r / min, the polishing time is 55min, and the polishing liquid flow rate is 10mL / min.

[0053] The polishing liquid is made of the following components in parts by weight: 15 parts of composite abrasive, 2 parts of oxidant, 8 parts of functional compound and 60 parts of water are mixed into a solution, and the pH value of the solution is adjusted to 4.5 with an organic acid; the composite abrasive is composed of aluminum oxide and functionalized silica sol in a mass ratio of 1:1; the aluminum oxide is spherical aluminum oxide, and the particle size of the spherical aluminum oxide is 80 nm; the oxidant is potassium permanganate; and the organic acid is oxalic acid.

[0054] The preparation method of functionalized silica sol is as follows:

[0055] S1. Add dopamine hydrochloride to the silica sol, disperse it evenly, add Tris solution, adjust the pH value of the solution to 8.5, place it at room temperature, stir and react for 28 hours to obtain polydopamine-modified silica sol; the particle size of nano-silica in the silica sol is 15 nm; the mass ratio of silica sol to dopamine hydrochloride is 1:0.15;

[0056] S2. Add the functional compound and triethylamine to the polydopamine-modified silica sol obtained in step S1, maintain the reaction temperature at 80°C, and reflux for 4.5 hours. After the reaction is completed, a functionalized silica sol is obtained; the mass ratio of the polydopamine-modified silica sol, the functional compound, and the triethylamine is 1:0.08:0.04.

[0057] Example 5

[0058] A polishing process for aluminum nitride ceramics comprises the following steps: placing an aluminum nitride ceramic substrate on a polishing pad, adding a polishing liquid for polishing; the polishing pad is a non-woven polishing cloth, and the polishing pressure is 200 g / cm 2 , the polishing speed is 90r / min, the polishing time is 50min, and the polishing liquid flow rate is 14mL / min.

[0059] The polishing liquid is made of the following components in parts by weight: 18 parts of composite abrasive, 4 parts of oxidant, 10 parts of functional compound and 65 parts of water are mixed into a solution, and the pH value of the solution is adjusted to 4 with an organic acid; the composite abrasive is composed of aluminum oxide and functionalized silica sol in a mass ratio of 1:1.5; the aluminum oxide is spherical aluminum oxide, and the particle size of the spherical aluminum oxide is 90nm; the oxidant is hydrogen peroxide; and the organic acid is citric acid.

[0060] The preparation method of functionalized silica sol is as follows:

[0061] S1, the same as step S1 in Example 3;

[0062] S2. Same as step S2 in Example 4.

[0063] Comparative Example 1

[0064] Compared with Example 2, the polishing liquid component in this comparative example does not contain a functional compound.

[0065] A polishing process for aluminum nitride ceramics comprises the following steps: placing an aluminum nitride ceramic substrate on a polishing pad, adding a polishing liquid for polishing; the polishing pad is a non-woven polishing cloth, and the polishing pressure is 300 g / cm 2 , the polishing speed is 90r / min, the polishing time is 50min, and the polishing liquid flow rate is 13mL / min.

[0066] The polishing liquid is made of the following components in parts by weight: 20 parts of composite abrasive, 4 parts of oxidant and 70 parts of water are mixed into a solution, and the pH value of the solution is adjusted to 4.5 with an organic acid; the composite abrasive is composed of aluminum oxide and functionalized silica sol in a mass ratio of 1:2; the aluminum oxide is spherical aluminum oxide, and the particle size of the spherical aluminum oxide is 100 nm; the oxidant is hydrogen peroxide; and the organic acid is tartaric acid.

[0067] The preparation method of the functionalized silica sol is the same as that in Example 2.

[0068] Comparative Example 2

[0069] Compared with Example 2, the composite abrasive in the polishing liquid component of this comparative example is composed of aluminum oxide and silica sol in a mass ratio of 1:2.

[0070] A polishing process for aluminum nitride ceramics comprises the following steps: placing an aluminum nitride ceramic substrate on a polishing pad, adding a polishing liquid for polishing; the polishing pad is a non-woven polishing cloth, and the polishing pressure is 300 g / cm 2 , the polishing speed is 90r / min, the polishing time is 50min, and the polishing liquid flow rate is 13mL / min.

[0071] The polishing liquid is made of the following components in parts by weight: 20 parts of composite abrasive, 4 parts of oxidant, 9 parts of functional compound and 70 parts of water are mixed into a solution, and the pH value of the solution is adjusted to 4.5 with an organic acid; the composite abrasive is composed of aluminum oxide and silica sol in a mass ratio of 1:2; the aluminum oxide is spherical aluminum oxide, and the particle size of the spherical aluminum oxide is 100 nm; the oxidant is hydrogen peroxide; and the organic acid is tartaric acid.

[0072] Comparative Example 3

[0073] Compared with Example 2, the polishing liquid component of this comparative example does not contain a functional compound, and the composite abrasive is composed of aluminum oxide and silica sol in a mass ratio of 1:2.

[0074] A polishing process for aluminum nitride ceramics comprises the following steps: placing an aluminum nitride ceramic substrate on a polishing pad, adding a polishing liquid for polishing; the polishing pad is a non-woven polishing cloth, and the polishing pressure is 300 g / cm 2 , the polishing speed is 90r / min, the polishing time is 50min, and the polishing liquid flow rate is 13mL / min.

[0075] The polishing liquid is made of the following components in parts by weight: 20 parts of composite abrasive, 4 parts of oxidant and 70 parts of water are mixed into a solution, and the pH value of the solution is adjusted to 4.5 with an organic acid; the composite abrasive is composed of aluminum oxide and silica sol in a mass ratio of 1:2; the aluminum oxide is spherical aluminum oxide, and the particle size of the spherical aluminum oxide is 100 nm; the oxidant is hydrogen peroxide; and the organic acid is tartaric acid.

[0076] After the polishing liquid used in Examples 2-5 and Comparative Examples 1-3 was placed for 3 months, the suspension stability of the polishing liquid was observed, and the survival of mold in the polishing liquid was measured (in percentage). The results are shown in Table 1.

[0077] Table 1 Polishing fluid properties

[0078]

[0079] It can be seen from the results in Table 1 that the polishing liquid used in Examples 2-5 of the present invention has good suspension stability and antibacterial performance; compared with Comparative Examples 1-3, functional compounds and functionalized silica sols are added to the polishing liquid components of Example 1 of the present invention, and polydopamine and functional compounds with antibacterial effects are grafted on the surface of silicon dioxide in the functionalized silica sol in sequence, and the functional compound structure contains a long-chain quaternary ammonium salt group with antibacterial and dispersing effects and a benzotriazole group with antibacterial effects. Therefore, the functional compounds and functionalized silica sols in the polishing liquid components can work synergistically, improve the dispersion stability of each component and the antibacterial performance of the polishing liquid, and jointly give the polishing liquid good suspension stability and antibacterial performance.

[0080] The thickness of the aluminum nitride ceramic substrates of Examples 2-5 and Comparative Examples 1-3 before and after polishing was measured using a thickness meter to determine the polishing rate of the polishing liquid; the surface roughness Ra was measured using an atomic force microscope, and the results are shown in Table 2.

[0081] Table 2 Polishing effect

[0082]

[0083] It can be seen from the results in Table 2 that the overall performance of the polishing process provided by Examples 2-5 of the present invention is far superior to that of Comparative Examples 1-3, with a higher polishing rate and good polishing effect, and an aluminum nitride ceramic substrate with small surface roughness and no scratches can be obtained; compared with Comparative Examples 1-3, functional compounds and functionalized silica sol grafted with functional compounds are added to the polishing liquid components of Example 1 of the present invention, wherein the functional compound structure contains a long-chain quaternary ammonium salt group with a dispersing effect and a benzotriazole group with a chelating ion effect, and the added functional compound and functionalized silica sol act synergistically to reduce ion contamination, so that each component exists uniformly and stably during the polishing process, and the role of the composite abrasive and the oxidant is fully exerted, which is helpful to improve the polishing rate and polishing effect, thereby obtaining an aluminum nitride ceramic substrate with better apparent quality.

[0084] It should be noted that, in this article, the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.

[0085] Although the embodiments of the present application have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present application, and that the scope of the present application is defined by the appended claims and their equivalents.

Claims

1. A polishing process for aluminum nitride ceramics, characterized in that: The polishing process The method comprises the following steps: placing an aluminum nitride ceramic substrate on a polishing pad and adding a polishing liquid for polishing; The polishing liquid is made of the following components by weight: 15-20 parts of composite abrasive, 2-4 parts of oxidant, 8-10 parts of functional compound and 60-70 parts of water are mixed into a solution, and the pH value of the solution is adjusted to 4-4.5 using an organic acid; The composite abrasive is composed of aluminum oxide and functionalized silica sol in a mass ratio of 1:1-2; The preparation method of the functionalized silica sol is: S1. Add dopamine hydrochloride to the silica sol, disperse it evenly, add Tris solution, adjust the pH value of the solution to 8.5, place it at room temperature, stir and react for 24-30 hours to obtain polydopamine-modified silica sol; S2, adding a functional compound and triethylamine to the polydopamine-modified silica sol obtained in step S1, maintaining the reaction temperature at 80° C., and reflux reacting for 4-5 hours. After the reaction is completed, a functionalized silica sol is obtained; The polishing liquid components and the functional compounds described in step S2 are: 。 2. The aluminum nitride ceramic polishing process according to claim 1, characterized in that: The particle size of the nano-silicon dioxide in the silica sol in step S1 is 10-20 nm; the mass ratio of the silica sol to dopamine hydrochloride is 1:0.1-0.

2.

3. The aluminum nitride ceramic polishing process according to claim 1, characterized in that: The mass ratio of the polydopamine-modified silica sol, the functional compound, and triethylamine in step S2 is 1:0.05-0.1:0.025-0.

05.

4. The aluminum nitride ceramic polishing process according to claim 1, characterized in that: The preparation method of the functional compound is: (1) Add 6-chloro-1-hydroxybenzotriazole and dodecyldimethyl tertiary amine to ethanol, maintain the reaction temperature at 80°C, and reflux for 10-12 hours. After the reaction is completed, cool to room temperature, remove ethanol, extract with dichloromethane and water, collect the aqueous phase, and concentrate under reduced pressure to obtain a modified compound with the structural formula: ; (2) Add the modified compound, 4-chlorobutyric acid and p-toluenesulfonic acid to toluene, maintain the reaction temperature at 110°C, reflux for 4-6 hours, and collect the water generated by the reaction with a water separator. After the reaction is completed, cool to room temperature, remove toluene, extract with dichloromethane and water, collect the aqueous phase, and concentrate under reduced pressure to obtain the functional compound.

5. The aluminum nitride ceramic polishing process according to claim 4, characterized in that: The molar ratio of 6-chloro-1-hydroxybenzotriazole and dodecyldimethyl tertiary amine in step (1) is 1:1.0-1.1; the molar ratio of the modified compound, 4-chlorobutyric acid and p-toluenesulfonic acid in step (2) is 1:1.0-1.1:0.03-0.

05.

6. The aluminum nitride ceramic polishing process according to claim 1, characterized in that: The oxidant is one or a mixture of hydrogen peroxide, sodium hypochlorite and potassium permanganate.

7. The aluminum nitride ceramic polishing process according to claim 1, characterized in that: The organic acid is one of tartaric acid, oxalic acid and citric acid or a mixture of several of them.

8. The aluminum nitride ceramic polishing process according to claim 1, characterized in that: The alumina is spherical alumina, and the particle size of the spherical alumina is 80-100 nm.

9. The aluminum nitride ceramic polishing process according to claim 1, characterized in that: In the polishing process, the polishing pad is a non-woven polishing cloth, and the polishing pressure is 200-300g / cm 2 , the polishing speed is 80-100r / min, the polishing time is 50-60min, and the polishing liquid flow rate is 10-15mL / min.

Citation Information

Patent Citations

  • Machine for casting lines of type

    CA112185A

  • Polishing solution for aluminum nitride ceramic substrate as well as preparation method and polishing method thereof

    CN112521866A

  • Odorless aluminum nitride polishing solution as well as preparation method and application thereof

    CN114672252A

  • Preparation method and application of dopamine / silicon dioxide composite aerogel

    CN112452262A

  • Stainless steel polishing solution as well as preparation method and application thereof

    CN115851135A